Differences in cause-specific mortality between healthcare workers and all other employees in Lithuania, 2011–2019 - Povilas Kavaliauskas; Domantas Jasilionis; Audrius Dulskas; Evaldas Kazlauskas; Giedre Smailyte (BMC Health Services Research)
Abstract Background Healthcare workers face health risks, including stress, burnout, and communicable diseases, leading to higher mortality rates. However, excess mortality diminishes with better disease control and lifestyle factors. Methods The study is based on the aggregated census-linked mortality dataset provided by Statistics Lithuania. The dataset was based on all 2011 census records, as well as death and emigration records from March 1, 2011, to December 31, 2019. The primary variable identified three groups: physicians, nurses and assistant nurses, and other healthcare workers. The reference groups consisted of individuals who were employed in all other sectors. We also conducted an analysis comparing highly educated healthcare workers to the highly educated workers in other sectors. The results are presented using age-adjusted sex-specific Poisson regression mortality rate ratios. Results The four most common causes of death among healthcare employees were cancer, cardiovascular deaths, other causes of death, and external causes of death. Female nurses show significantly lower 0.86 (0.74–0.99) mortality due to malignant neoplasms than all other employees. Male physicians had lower mortality rates from smoking-related cancer (0.47 (0.24–0.95)); however, significantly higher mortality was found for digestive system diseases 6.29 (2.36–16.79) and liver diseases 5.1 (1.27–20.42). Highly educated male healthcare workers had 1.3–1.4 times higher all-cause, cardiovascular, and malignant neoplasm mortality than highly educated workers from all other sectors. Highly educated females working in health care had lower mortality for malignant neoplasms but significantly higher mortality for all other causes of death. Conclusions Excess mortality due to digestive system diseases and alcohol-related causes of death among nurses and other health care employees is a particular matter of concern and should be addressed by appropriate prevention policies. Further in-depth studies on risk factors are needed to explain mortality differences between the groups of healthcare and other sector employees in Lithuania.